Emission profiles of PM10-bound polycyclic aromatic hydrocarbons from biomass burning determined in chamber for assessment of air pollutants from open burning - Wan Wiriya (2018)
© Taiwan Association for Aerosol Research. In order to estimate emission factors (EFs) of air pollutants, three types of biomass (rice straw, maize residue and leaf litter) were collected and burnt in a self-designed stainless steel chamber. The EFs of PM10 from biomass burning were leaf litter (1.22 ± 0.29 g kgdry–1) > rice straw (0.89 ± 0.25 g kgdry–1) > maize residue (0.59 ± 0.13 g kgdry–1), while those of PM10-bound polycyclic aromatic hydrocarbons (PAHs) were leaf litter (0.91 ± 0.28 mg kgdry–1) > maize residue (0.47 ± 0.11 mg kgdry–1) ~ rice straw (0.46 ± 0.21 mg kgdry–1). The results revealed that burning of forest leaf litter emitted higher amounts of particulate pollutants than the agricultural residue burning. New values of diagnostic ratios of some PAHs, including FLA/(FLA + PYR, BaA/(BaA + CHR) and IND/(IND + BPER), were proposed to identify biomass burning sources. Emission rates (ERs) of PM10 and PAHs from biomass burning in Chiang Mai, Thailand were estimated based on the EFs and burning areas recorded in the dry season of 2010 and 2011. The ERs of pollutants from forest burning were found to be much higher than those from agricultural field burning, mainly due to larger burnt areas in the forest. In 2010, PM10 was mainly emitted from the forest fire (2,250 tons), followed by crop burning (133 tons) and paddy field burning (66.9 tons). The same trend was found in 2011 but with much lower emission rates. The ERs of PAHs from biomass burning were 1,815 kg in 2010 and 416 kg in 2011. The ERs of PM10and PAHs in 2011 were 77% decreased from those in 2010 due to unusually high precipitation in the dry season, causing relatively smaller burnt areas and lower pollutant emissions from open burning. It is expected that the results from this study will be significant information for regulatory actions of air quality management in the northern part of Thailand.